Photographic manual of regional orthopaedic and neurological tests - Cipriano, Joseph J. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
"Now in its Fifth Edition, this Photographic Manual of Regional Orthopaedic and Neurologic Tests describes in step-by-step fashion how to perform these tests. Each chapter begins with a decision tree of the orthopaedic examination of an anatomic area, followed by a brief description of the anatomic area, usually with an accompanying drawing. The presentation of each test begins with a clinical description and a box of clinical signs and symptoms, followed by a brief description of the procedure with a photograph demonstrating the position of the clinician and the patient. The author then presents a brief rationale for the test and suggests diagnostic imaging procedures where appropriate. An accompanying DVD demonstrates a typical examination"--Provided by publisher.